2017
DOI: 10.3390/su9081385
|View full text |Cite
|
Sign up to set email alerts
|

Directive 2014/95/EU: Are Italian Companies Already Compliant?

Abstract: According to Directive 2014/95/EU on disclosure of non-financial information from 2017 onwards, large companies (exceeding 500 employees) headquartered in Member States will be required to provide a series of social, environmental, and governance statements. The Directive was transposed into Italian law by Legislative Decree 254 of 30 December 2016.The aim of this paper is to evaluate the information gap for Italian companies and, consequently, the adjustments required by the new Directive on non-financial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
161
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 59 publications
10
161
3
8
Order By: Relevance
“…The largest difference concerns certain categories, such as human rights and anti-corruption. Our finding is consistent with Italian evidence [19], which indicated that the quality of non-financial information disclosure is much higher in voluntary CSR reports than in mandatory annual reports.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The largest difference concerns certain categories, such as human rights and anti-corruption. Our finding is consistent with Italian evidence [19], which indicated that the quality of non-financial information disclosure is much higher in voluntary CSR reports than in mandatory annual reports.…”
Section: Discussionsupporting
confidence: 82%
“…According to the new regulations, only some non-financial information may by omitted, being exceptions rather than the general rule. The results of the research allow us to state that the level of compliance of Polish companies is low compared to that of Italian companies, which show an average non-financial information score of about 49% [19].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations